Optimal Workfare with Voluntary and Involuntary Unemployment - Claus Thustrup Kreiner; Torben Tranæs (University of Copenhagen, Economic Policy Research Unit (EPRU), 2003)
This paper studies whether a benevolent government should use workfare as part of its unemployment benefit policy. We consider a population composed of employed and unemployed workers as well as individuals who do not seek employment. Job search behavior is private information implying that voluntarily unemployed individuals can claim unemployment insurance (UI) benefits intended for unemployed workers. As a consequence, pecuniary benefit schemes underinsure workers against unemployment. We show that requiring unproductive activities (workfare) in exchange for UI benefits may create a Pareto improvement by facilitating better unemployment insurance for workers, and we characterize the situations where this is the case.
Keywords: H2; J65; 330; unemployment insurance; workfare; Pareto optimality; Aktivierende Sozialhilfe; Arbeitslosigkeit; Pareto-Optimum